2016
DOI: 10.1093/jjco/hyw063
|View full text |Cite
|
Sign up to set email alerts
|

Influence of positive peritoneal cytology on prognostic factors and survival in early-stage endometrial cancer: a systematic review and meta-analysis

Abstract: Objective: The prognostic significance of positive peritoneal cytology in patients with early-stage endometrial cancer (Stage 1 or 2) is controversial and perhaps depends on the presence of other factors. The relationship of other prognostic factors with positive peritoneal cytology remains unclear. This study aimed to investigate the association between positive peritoneal cytology and prognostic factors and the influence of positive peritoneal cytology on survival in patients with early-stage endometrial can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(23 citation statements)
references
References 21 publications
3
19
1
Order By: Relevance
“…In the FIGO 2009 staging system, peritoneal cytology is not associated with clinical stage, and positive peritoneal cytology is indeed not considered as an independent prognostic factor in endometrial cancer. However, some reports have shown a relation between positive peritoneal cytology and poor prognosis in patients with early stage endometrial carcinoma [920]. Although MI is considered to be among the most important prognostic factors for endometrial cancer, multivariate analysis in our study showed no association between MI and prognosis.…”
Section: Discussioncontrasting
confidence: 81%
“…In the FIGO 2009 staging system, peritoneal cytology is not associated with clinical stage, and positive peritoneal cytology is indeed not considered as an independent prognostic factor in endometrial cancer. However, some reports have shown a relation between positive peritoneal cytology and poor prognosis in patients with early stage endometrial carcinoma [920]. Although MI is considered to be among the most important prognostic factors for endometrial cancer, multivariate analysis in our study showed no association between MI and prognosis.…”
Section: Discussioncontrasting
confidence: 81%
“…However, other studies found that, in low-risk patients with EC, positive peritoneal cytology did not affect the 5year disease-free survival rate [24,25]. Positive peritoneal cytology has also previously shown no effects on overall survival or disease-free survival in patients with low-or intermediate-risk disease [26,27]. In the present study, we found that positive peritoneal cytology was a critical and independent prognostic factor of EC recurrence in both cohorts.…”
Section: Journal Of Oncologysupporting
confidence: 52%
“…Given that peritoneal cytology is not a part of surgical staging, the relationship between survival and peritoneal cytology particularly is still very controversial in early-stage patients. While some studies showed positive peritoneal cytology is related to high rates of recurrences and poor survival ( 7 , 10 , 11 ), some found out no relationship between positive peritoneal cytology and survival ( 28 , 29 ). Seagle et al ( 30 ) analyzed data from the National Cancer Database and reported that adjuvant CT provides better survival in patients who were diagnosed as an early endometrioid type of endometrial cancer patients with positive peritoneal cytology.…”
Section: Discussionmentioning
confidence: 99%